2015
DOI: 10.1093/jac/dkv150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations associated with clofazimine resistance inMycobacterium tuberculosis: Table 1.

Abstract: Mutations in rv0678 are a major mechanism of clofazimine resistance. Our findings provide useful information for the design of new molecular tests for rapid detection of clofazimine resistance. Further studies are needed to address the role of rv1979c and rv2535c in clofazimine resistance and mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 36 publications
2
112
0
1
Order By: Relevance
“…Mutations in the start codon (M1A) may prevent translation of the MAB_4384 transcript. Similar mutations in the start codon were reported earlier in Rv0678, the repressor of MmpS5-MmpL5 in M. tuberculosis, and account for resistance to clofazimine in strains selected in vitro for clofazimine resistance (45). A recent report also highlighted the presence of the same start codon mutation (replacement of N-formylmethionine by alanine) in Rv0678 in a clinical isolate from a multidrug-resistant TB patient following bedaquiline treatment (46).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Mutations in the start codon (M1A) may prevent translation of the MAB_4384 transcript. Similar mutations in the start codon were reported earlier in Rv0678, the repressor of MmpS5-MmpL5 in M. tuberculosis, and account for resistance to clofazimine in strains selected in vitro for clofazimine resistance (45). A recent report also highlighted the presence of the same start codon mutation (replacement of N-formylmethionine by alanine) in Rv0678 in a clinical isolate from a multidrug-resistant TB patient following bedaquiline treatment (46).…”
Section: Discussionsupporting
confidence: 70%
“…A recent report also highlighted the presence of the same start codon mutation (replacement of N-formylmethionine by alanine) in Rv0678 in a clinical isolate from a multidrug-resistant TB patient following bedaquiline treatment (46). Although highly reminiscent of the mechanisms accounting for resistance to azoles, clofazimine, and bedaquiline in M. tuberculosis that together implicate a wide panel of mutations in the regulator, causing overexpression of the MmpS5-MmpL5 efflux pump, a major difference resides in the nature of the regulators involved (34,35,(45)(46)(47). Whereas Rv0678 is a member of the MarR family of regulators (48), MAB_4384 belongs to the TetR family, and the change in the induction level of mmpS5-mmpL5 in the M. abscessus mutants was found to be much more pronounced than those found in M. tuberculosis (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (29) recently reported in vitro selection of a pepQ mutant in M. tuberculosis with clofazimine. However, they did not report the results of direct susceptibility testing with clofazimine or bedaquiline or confirm the causative role of pepQ mutation in clofazimine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in Rv0678, which encodes the MarR-like transcriptional regulator of the MmpS5-MmpL5 efflux system, were shown to cause cross-resistance between clofazimine and bedaquiline in vitro (9,10). Indeed, mutations in Rv0678 were the major mechanism of clofazimine resistance among isolates selected with clofazimine in vitro (9,11). During clinical trials of bedaquiline, isolates with reduced susceptibility to bedaquiline were shown to have Rv0678 mutations and cross-resistance to clofazimine (10,12).…”
mentioning
confidence: 99%